The Greek War of Independence from the Perspective of Historical Sociology - Lekas, Padelis E. (The Historical Review/La Revue Historique, 2006)
This is an attempt to place the Greek War of Independence in the wider context of the clash between Tradition and Modernity in the European periphery. It focuses on the ideology and the movement of nationalism - a phenomenon springing up in modernity and bringing forward the concept of the nation as the proper unit of state organisation. Being the undisputed offspring of nationalism (which is viewed here as both the product and the vehicle of modernisation), the Greek War of Independence is discussed not solely in its political dimensions but also in terms of its contribution to a much broader societal change. It is in this sense that the Greek struggle for independence may be interpreted as the specifically "Greek exit" from tradition - as an undoubtedly unique event of momentous importance per se, yet, on the other hand, as one more instance in a prolonged and very intricate process of societal transformations.